Produção de miniestacas, brotação de tubérculos e desempenho agronômico de clones de batata - Batistel, Sorhaila Camila (2018)
The present study had as objective to study the production of mini-cuttings and the budding of tubers of potato clones stored under different conditions. An experiment was carried out to evaluate the effect of two plant densities (128 and 400 plants per square meter) on the yield of mini-cuttings of four potato clones (Macaca, SMINIA73101-3, SMINIA05011-3 and SMINIA06066-10) and the ideal number of collections in spring 2016 and fall 2017. An experiment was carried out to evaluate the dormancy and apical dominance of three potato clones (Asterix, SMINIA793101- 3 and SMINIA00017-6) two tuber sizes ( <35mm and> 35mm) sprayed with three doses (0, 15 and 30 g L-1) of gibberellic acid (GA) and stored under two temperatures (10ºC and 20ºC) for 81 days. Another experiment was carried out with these same tubers and treatments in the field. Tubers were planted at the density of three hills per linear meter and spacing of 0.80 m between rows. Number of days until emergence, number of stems, stem length, number of large and medium tubers and fresh mass of large and medium tubers were evaluated. The 400 plants per square meter resulted in the highest productivity of mini-cuttings. Macaca had the highest mini-cutting production in the spring, with three harvest considered ideal, for both spring and autumn seasons. Potato clones differed for dormancy and apical dominance. Spaying tubers with GA tubers accelerates sprouting and plant emergence in the field. The dormancy is lower in tubers stored under higher temperature. Larger tubers have smaller dormancy, but managing GA and storage temperature it is possible to standardize sprouting. Larger tubers have a larger number of stems, longer stems and higher yield in the field.